TINDAK KEKERASAN YANG DILAKUKAN ANAK-ANAK SEBAGAI UPAYA UNTUK MEMECAHKAN MASALAH YANG DIAKIBATKAN TEKANAN LINGKUNGAN - Witrin Gamayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2009)
Violent behaviors conducted by children were unimaginable by our mind that we have set our mind that children are group of people who still innocent, and the hope for our future. Violence—in our mind—is perhaps the trait that labeled to some thugs, robbers, and many criminals whose world are full of violence they lived in. What is happening with our society and our children? Violence conducted by children can be seen as social behavior disturbance since there are violations to the moral values and humanity, family and society normative rules. Violent behavior—verbal and non verbal—including bad attitudes and behaviors that disturb many our environment are violation to what we call as society norms and laws. Children who conducted violent behavior were not a result of instant process but a cumulative result of many aspects they have seen, heard and felt in daily life. Aggression and anti social behavior are a learned behavior which means that children learned it from imitation process from something and someone who they meet, see, heard and copied.